Conservation genetics of the franciscana dolphin in Northern Argentina: population structure, by-catch impacts, and management implications - Mendez, Martin; Rosenbaum, H. C; Bordino, P (Conservation genetics, 2008)
Evaluating population structure in the marine environment is a challenging task when the species of interest is continuously distributed, and yet the use of population or stock structure is a crucial component of management and conservation strategies. The franciscana dolphin (Pontoporia blainvillei), a rare endangered coastal cetacean, suffers high levels of by-catch all along its distribution range in the Western South Atlantic, and questions have been raised about boundaries or divisions for population management. Here we apply genetic tools to better understand population structure and migration, sex-biased dispersal, and to assess potential genetic and demographic impacts of by-catch. Our analyses, based on mtDNA control region sequences, reveal significant genetic division at the regional level and fine-scale structure within our study area. These results suggest that the population in northern Buenos Aires is the most isolated population in Argentina. We found no significant departure from an equal sex ratio among the by-caught animals. A few cases of multiple entanglements appeared to be mother-calf pairs based on field observations and individuals sharing the same mtDNA control region lineage. The distribution of haplotype frequencies observed could imply that some maternal lineages are more prone to be subject to higher rates of by-catch, although biopsy sampling is necessary to fully evaluate whether maternal lineage distributions are the same for biopsy sampled and by-caught animals. A genetic indication of population size disequilibrium was detected for all populations in Argentina, which is consistent with available rates of by-catch and abundance estimates. Collectively, our findings support the current scheme of larger recognized Franciscana Management Areas (FMA), but argue for a finer-scale subdivision within Northern Buenos Aires region (FMA IV). Finally, an integrated approach to promote conservation of this endangered small cetacean has to involve identification of genetic and demographic threats, a more sustainable fishery strategy to reduce by-catch, and designation of protected areas that are supported by underlying population structure for franciscana dolphins.